Development of Jigsaw-Based Student Worksheets (LKPD) to Improve Mathematics Learning Outcomes of Fifth Grade Elementary School Students - Bismi Bismi; Ismira Ismira; Alfroki Martha (FKIP - Universitas Riau, 2026)
This study produced a Student Worksheet (LKPD) developed using the Jigsaw learning model for fifth-grade mathematics in elementary schools. The product went through a validation stage, showing results in the very valid category, meaning that the LKPD is suitable for use in learning activities. Practicality tests were conducted involving both teachers and students, and the findings indicated that the worksheet is easy to understand, simple to use, and relevant to the learning objectives. In addition, the effectiveness of the LKPD was assessed by comparing student outcomes before and after implementation. The results showed a significant improvement, with the percentage of students achieving mastery increasing from 35% in the pretest to 80% in the posttest. This indicates that the LKPD successfully supports student engagement and comprehension in mathematics. Overall, the Jigsaw-based worksheet can serve as an effective learning medium that not only facilitates collaboration but also enhances student achievement in mathematics learning at the elementary school level.